Development Of Fiqh Learning Media For Tenth-Grade Students - Iin Baroroh Maarif; Hidayatur Rohmah; Hamidah (SCHOOLAR: Social and Literature Study in Education, 2024)
Teachers who have high creativity always try to make the learning process interesting for their students; it could be by using various methods such as using learning media. The use of learning media in the teaching and learning process greatly influences students' learning interest, the emergence of motivation and stimulation in learning, and even brings psychological influences on students. Therefore, the use of learning media at the teaching orientation stage will greatly help the effectiveness of the learning process, so that the goals of learning can be achieved optimally. For this reason, based on the potential and existing problems, researcher try to develop one of the learning media. In this development, the media used is power point based media. The development of this power point-based learning media be developed in learning Fiqh for Class X at MAN 4 Jombang. Validity is illustrated by the results of the validator's assessment, where validator 1's validation results obtain an average of 87.5% and validator 2 obtains an average of 96.8%. So it can be concluded that the average of the two validators is 80% and is included in the good category. Keywords: Development, Fiqh, Learning media, Students